2020
DOI: 10.3390/su12166528
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Comparison between Alternative Rice Farming Systems in Tanzania Using a Monte Carlo Simulation Approach

Abstract: Tanzania is the second-largest producer of rice (Oryza sativa) in Eastern, Central, and Southern Africa after Madagascar. Unfortunately, the sector has been performing poorly due to many constraints, including poor agricultural practices and climate variability. In addressing the challenge, the government is making substantial investments to speed the agriculture transformation into a more modernized, commercial, and highly productive and profitable sector. Our objective was to apply a Monte Carlo simulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The parameter also indicates that adopting SRI in rice cultivation could increase the rice yield of farm households by about 15.1%. This result is in line with the studies of Varma (2019), Kadigi et al (2020), Mishra et al (2021), and Barrett et al (2022), who found that SRI adoption could increase rice yields through an estimated econometric model.…”
Section: The Impact Of Sri Adoption On Rice Yieldssupporting
confidence: 92%
“…The parameter also indicates that adopting SRI in rice cultivation could increase the rice yield of farm households by about 15.1%. This result is in line with the studies of Varma (2019), Kadigi et al (2020), Mishra et al (2021), and Barrett et al (2022), who found that SRI adoption could increase rice yields through an estimated econometric model.…”
Section: The Impact Of Sri Adoption On Rice Yieldssupporting
confidence: 92%
“…The commonly used undergrowth crops in the agroforestry system are food-producing plants, for example, rice. Rice has a high economic value for the community, either selfconsumed or as cash income (Nurliza et al 2017;Kadigi et al 2020). Several types of sengon trees have been planted in Indonesia, including two types of origins, namely local sengon and Solomon sengon.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation was also applied to support seeding and harvesting decisions in two recent studies. Kadigi et al [26] performed simulation experiments to evaluate alternative rice farming systems, specifically, traditional rice farming practices and the proposed rice intensification (SRI) practices, to improve farmers' income. Deepradit et al [27] presented a simulation model for aromatic coconut manufacturing to determine an appropriate harvest amount and harvesting age that maximize annual profit under uncertainty.…”
Section: Literature Reviewmentioning
confidence: 99%